Wearing a happy mask: mother's expressions of suicidality with postpartum depression. Issue 4 (3rd July 2020) - Praetorius, Regina; Maxwell, December; Alam, Komal
ABSTRACT: Anywhere between 7% to 63% of mothers will experience postpartum depression (PPD) globally. Currently, the leading cause of maternal death after the birth of a child is suicide; the psychache or intolerable psychological pain that precedes suicide may have been exacerbated by PPD. Despite research quantitatively evaluating risk factors of suicidality for those experiencing PPD, less is known about the lived experiences of mothers who experience thoughts of self-harm in the postpartum period. This study utilized Qualitative Interpretive Meta-Synthesis (QIMS), to investigate the question "What are the lived experiences of mothers with postpartum depression who experience suicidality?" The purpose of this study was to synthesize the lived experiences specific to suicidal ideation in the postpartum period to highlight shared experiences to influence future research, PPD screening approaches, and clinical interventions. Results included six themes: 1. I wear a happy mask, 2. Motherhood is not as it seems, 3. Losing control, 4. Sinking ship, 5. Sleep makes it worse, and 6. Sharing stories and chores. A further theoretical reduction resulted in the alignment of the existing Interpersonal Theory of Suicide to postpartum depression-specific suicidality as a part of the results.